Clonostachys rosea BAFC3874 as a Sclerotinia sclerotiorum antagonist: mechanisms involved and potential as a biocontrol agent - Rodriguez, Maria Alejandra (2011)
Aims: To establish the modes of action of the antagonistic fungal strain Clonostachys rosea BAFC3874 isolated from suppressive soils against Sclerotinia sclerotiorum and to determine its potential as a biocontrol agent. Methods and Results: The antagonistic activity of C. rosea BAFC3874 was determined in vitro by dual cultures. The strain effectively antagonized S. sclerotiorum in pot-grown lettuce and soybean plants. Antifungal activity assays of C. rosea BAFC3874 grown in culture established that the strain produced antifungal compounds against S. sclerotiorum associated with secondary metabolism. High mycelial growth inhibition coincided with sclerotia production inhibition. The C. rosea strain produced a microheterogeneous mixture of peptides belonging to the peptaibiotic family. Moreover, mycoparasitism activity was observed in the dual culture. Conclusions: Clonostachys rosea strain BAFC3874 was proved to be an effective antagonist against the aggressive soil-borne pathogen S. sclerotiorum in greenhouse experiments. The main mechanisms involve peptaibiotic metabolite production and mycoparasitism activity. Significance and Impact of the Study: Clonostachys rosea BAFC3874 may be a good fungal biological control agent against S. sclerotiorum. In addition, we were also able to isolate and identify peptaibols, an unusual family of compounds in this genus of fungi.